Assessing the potential of a Virtual Patient Advocate to provide preconception care and health advice to women living in Australia. (20th April 2021) - Walker, Ruth; Drakeley, Sheila; Julce, Clevanne; Sidduri, Nireesha; Bickmore, Timothy; Skouteris, Helen; Jack, Brian; Boyle, Jacqueline
Abstract: A preconception Virtual Patient Advocate (VPA) called "Gabby" supported African-American women to decrease their preconception health risks and may be a scalable resource to increase women's access to preconception care. Aims were to assess the acceptability of a preconception VPA in women living in Australia and document the changes required to adapt Gabby to suit an Australian context. Taking a descriptive qualitative approach, nonpregnant female participants ( n = 31), aged 18–45 years, living in metropolitan and regional Victoria, Australia interacted with Gabby. Focus groups ( n = 7) that gathered participants' perspectives of their experience with Gabby ran in July–August 2019 before being transcribed verbatim and thematically analyzed. Six interrelated themes and 12 subthemes were identified. Participants found VPAs to be an acceptable provider of health information with potential to increase women's access preconception health advice. Gabby was considered to be trustworthy and was able to develop rapport with participants in a relatively short time. Context-specific, relevant, tailored and trustworthy information and advice were considered more important that Gabby's physical appearance. Participants had strong opinions about potential technological advancements (e.g., reminders and rewards) and addressing navigation issues to increase Gabby's acceptability. Participants envisaged that they would use Gabby for readily available and evidence-based information before seeking advice from a health professional if required. Overall, the concept VPAs to provide preconception advice and Gabby were acceptable to participants. Future development of VPAs, Gabby, and other online technology-based resources should consider women's high expectations of the online health information they choose to interact with.